Effect of the Mid-Layer on the Diversion Length and Drainage Performance of a Three-Layer Cover with Capillary Barrier - Fidan, Aysenur Aslan; Berilgen, Mehmet Muhit (MDPI, 2024)
The capillary barrier is a type of soil cover system commonly used in various geotechnical applications, such as limiting infiltration for slopes or landfills or providing cover for solid waste. It serves to prevent the movement of water through the soil layers by utilizing contrasting particle sizes. This paper focuses on investigating the effect of the granular layer on the performance of a three-layer cover with a capillary barrier, integrating the granular layer within clayey sand. The investigation involved one-dimensional infiltration tests utilizing four uniform granular soils with varying grain sizes. These tests were instrumental in calibrating soil water characteristic curves and hydraulic conductivity curves via back analysis. Subsequently, numerical analyses were conducted using a 15 m long model for each of the four distinct cover types. The results indicated that the fine gravel significantly improved the barrier performance beyond one-dimensional tests, owing to its high permeability and the influence of the slope. After the capillary barrier failure, the intermediate layers transitioned into efficient drainage layers, particularly in the gravel layer with the highest lateral drainage capacity. Clayey sand at the bottom delayed percolation, thereby supporting the conversion of the intermediate layer into an effective drainage component. Overall, the multi-layer system showed superior percolation performance compared to the clayey sand cover lacking a granular layer.
Keywords: three-layer cover system; capillary barrier; precipitation; diversion length; lateral drainage; water balance; unsaturated transient seepage analysis; HYDRAULIC CONDUCTIVITY; PHYSICAL MODEL; FIELD DATA; SOIL; DESIGN; INFILTRATION; PREDICTIONS; HYSTERESIS; CAPACITY; FLOW; Chemistry; Engineering; Materials Science; Physics